Przedsiębiorstwa publiczne w procesie integracji europejskiej - Olszewska, Barbara; Olszewski, Leon (Public Enterprises in the Process of European Integration, 2008)
The authors highlight the problems of evolution of the role of public enterprises in the process of European integration. The progressive liberalization of European economy during the second half of the 20th century has limited the role of public enterprises in the national economy particularly its strategic function and social objectives. The authors stress the importance of Maastrich Treaty and Amsterdam Treaty to development of the legal framework of the competition policy and practical application of State aid. The paradigm of regulatory practices of public sector enterprises is change to new market regulation. First of all, European Commission supervises the functioning of the Internal Market. Public sector must follow transparent open procedures ensuring conditions of competition. In the authors' opinion, the replacement of social mission logic, characteristic of the European economies, by effectiveness logic implies difficult dilemma for the State. Development strategy of national economy does not always comply with the vision of the EU development created by European Commission and other European institutions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 80-90